2017
DOI: 10.3390/ijerph14050489
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Coal Workers’ Pneumoconiosis (CWP) Patients in a State-Owned Mine in the East of China from 1963 to 2014

Abstract: To investigate the mortality probability, life expectancy of coal workers’ pneumoconiosis (CWP), and related factors of life expectancy, a total of 495 patients with CWP were diagnosed and reported from 1963 to 2014 in a state-owned mine in the east of China. The life table method, log rank method, and Cox regression model were used for survival analysis. 95 out of 495 CWP died during this period. The mortality rate was 19.19%. The average life span was 12.1 (0.0–33.2) years and average death age was 57.4 (33.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 23 publications
1
24
0
2
Order By: Relevance
“…CWP patients without pulmonary TB showed higher than patients with pulmonary TB for survival, and a significant difference was observed in the survival curves between these two groups. Cox regression model for evaluation using risk factors, dust exposure years, an age of onset and first diagnostic stage indicated that prevention and treatment of CWP complication are important for patient survival rates (Han et al, 2017).…”
Section: Chronic Lower Respiratory Diseasementioning
confidence: 99%
“…CWP patients without pulmonary TB showed higher than patients with pulmonary TB for survival, and a significant difference was observed in the survival curves between these two groups. Cox regression model for evaluation using risk factors, dust exposure years, an age of onset and first diagnostic stage indicated that prevention and treatment of CWP complication are important for patient survival rates (Han et al, 2017).…”
Section: Chronic Lower Respiratory Diseasementioning
confidence: 99%
“…In this paper, we investigated the case where the data is masked and the failure time is partly interval-censored (PIC) using the Bayesian approach. We employed the Cox proportional hazards model, which is used extensively but mostly for public health studies; see, for example, Han et al [16] and Liu et al [17]. e rest of the paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the survival of patients with pneumoconiosis is not sufficient 9 10. One survival analysis of CWP patients in a state-owned mine in the east of China from 1963 to 2014 showed that the average survival was 12.1 years after diagnosis of CWP and the average death age was 57.4 years 11. Another analysis of patients in Changsha from 1956 to 2010 pointed out the life expectancy was 60.12 years 12.…”
Section: Introductionmentioning
confidence: 99%